2016
DOI: 10.3892/ijo.2016.3576
|View full text |Cite
|
Sign up to set email alerts
|

CREBRF is a potent tumor suppressor of glioblastoma by blocking hypoxia-induced autophagy via the CREB3/ATG5 pathway

Abstract: Hypoxia induces protective autophagy in advanced glioblastoma cells, and targeting this process may improve the outcome for glioblastoma patients. Recent studies have suggested that the autophagic process is upregulated in glioblastoma cells in response to extensive hypoxia. Here, we describe a novel tumor suppressor in glioblastoma cells, whereby hypoxia downregulated CREBRF expression and acts as a potent inhibitor of autophagy in glioblastoma cells via the CREB3/ATG5 pathway. Our results demonstrate that CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…However, the function of CREBRF is minimally characterized, so the mechanisms by which rs373863828 affects these phenotypes are currently unclear. Individual studies have indicated that this transcription factor impacts glucocorticoid signaling, autophagy, unfolded protein response, and starvation resistance, as well as murine decidualization, embryo implantation, and maternal behavior (Audas, Li, Liang, & Lu, 2008; Li et al, 2016; Martyn et al, 2012; Minster et al, 2016; Xue et al, 2016; Yang et al, 2013). Future studies should aim to refine the effect of this variation on the related phenotypes of height, weight, and BMI in other Pacific Island populations, as well as other anthropometric traits.…”
Section: Discussionmentioning
confidence: 99%
“…However, the function of CREBRF is minimally characterized, so the mechanisms by which rs373863828 affects these phenotypes are currently unclear. Individual studies have indicated that this transcription factor impacts glucocorticoid signaling, autophagy, unfolded protein response, and starvation resistance, as well as murine decidualization, embryo implantation, and maternal behavior (Audas, Li, Liang, & Lu, 2008; Li et al, 2016; Martyn et al, 2012; Minster et al, 2016; Xue et al, 2016; Yang et al, 2013). Future studies should aim to refine the effect of this variation on the related phenotypes of height, weight, and BMI in other Pacific Island populations, as well as other anthropometric traits.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 7 genes CREBRF, DIXDC1, AHNAK, CYBRD1, NOSTRIN, TNS2 and TNFSF12 were negatively correlated with the strongly interconnected cell cycle and mitosis clique. Indeed, a number of these genes have been identified as candidate tumor suppressor genes including CREBRF, DIXDC1, AHNAK and TNS2 [4952]. Furthermore, NOSTRIN was found to be a potential negative regulator of disease aggressiveness in pancreatic cancer and CYBRD1 was identified as part of an iron regulatory gene signature that predicts outcome in BC [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…First, topological analysis was conducted on the network, and the graph parameters indicated six lncRNAs and seven mRNAs as the hub nodes in the regulatory network. Among these genes, CAMTA1, CDC42 and RNF138 have been reported as oncogenes in multiple cancers, while CREBRF was a tumor suppressor in glioblastoma and a tumor promoter in gastric cancer . Furthermore, CAMTA1 and CDC42 could interact with several lncRNAs to make significant effects on the tumorigenesis …”
Section: Discussionmentioning
confidence: 99%